Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1021/acs.est.9b05394
|View full text |Cite
|
Sign up to set email alerts
|

Erosion Behavior of Different Microplastic Particles in Comparison to Natural Sediments

Abstract: Microplastic (MP) has been detected in marine, limnic, terrestrial, and atmospheric environments. However, rivers are often only seen as transport paths for MPs from inland sources to the oceans, although transport rates in rivers can hardly be determined yet. MP in rivers can either be transported, or it settles to the bottom of the river and either remains there or is remobilized again at higher flow velocities. This remobilization, also known as erosion, depends on the critical shear stress of a particle an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(122 citation statements)
references
References 32 publications
3
112
0
Order By: Relevance
“…and Waldschläger and Schüttrumpf (2019b) for the critical shear stress. The restriction of our approach to the 20-500 µm size class results from model limitations.…”
Section: Model Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…and Waldschläger and Schüttrumpf (2019b) for the critical shear stress. The restriction of our approach to the 20-500 µm size class results from model limitations.…”
Section: Model Approachmentioning
confidence: 99%
“…It is well known, that beside density, shape and size play an important role for the sinking velocity (e.g.,; Kowalski et al, 2016;Kooi and Koelmans, 2019). Waldschläger and Schüttrumpf (2019a;2019b) provide an overview of data and formulas, which were adapted by us. However, differences in shape and size did not play an important role for the temporal and spatial resolution we used in our model approach.…”
Section: Uncertainties and Limitationsmentioning
confidence: 99%
“…The results demonstrated a decrease in MP concentration downstream from 0.76 particles/L (P3) to 0.13 particles/L (P2), to the lowest concentration of 0.11 particles/L (P4). This decrease can be explained by the retention of MP by sediment as a common process of MP transport in fluvial systems [46]. Since there was a very low flow rate in the Adyar River during sampling, no remobilisation could have taken place with an increasing flow velocity [46][47][48].…”
Section: Resultsmentioning
confidence: 99%
“…The findings of the current study relate primarily to the transport behavior of spherical MP particles, with diameters larger than that of the surrounding sediment (except MP "B"). It is known that the ratio of the size between plastic particles and the surrounding sediment has an influence on the transport behavior (Waldschläger and Schüttrumpf, 2019b;Sebille et al, 2020) because if, for example, the particle size is smaller than the sediment grain size, the initiation of movement depends on the particle orientation to the flow.…”
Section: Discussionmentioning
confidence: 99%
“…It was proven that stormy winds, surface waves and sea level variations govern the occurrence and deposition of MP within the sandy body of beaches instead of anthropogenic loads (Chubarenko et al, 2018b). For the initiation of movement and entrainment of MP particles, the particle size and density in correlation with the sediment properties were more important than the particle shape (Ballent et al, 2013;Waldschläger and Schüttrumpf, 2019b). It was recently found that the infiltration depth increases with decreasing MP particle diameter and that spherical particles infiltrate deeper than fragments and fibers (Waldschläger and Schüttrumpf, 2020).…”
Section: Introductionmentioning
confidence: 99%